Cover Picture: NIR‐II Fluorescence imaging for cerebrovascular diseases (View 6/2021). Issue 6 (17th December 2021) - Ren, Feng; Jiang, Zhilin; Han, Mengxiao; Zhang, Hao; Yun, Baofeng; Zhu, Hongqin; Li, Zhen
Abstract : In this article number 20200128, Zhen Li and co‐workers have summarized the recent advances of the NIR‐II fluorescence imaging technique, and addressed its significance in the early prevention and treatment of cerebral diseases inclusive of traumatic brain injury (TBI), stroke, and cerebroma. The advanced NIR‐II fluorescence imaging system and nano‐fluorophores enable the dynamic and visible evaluation of cerebral lesions from tissue, cellular and molecular levels.